(untitled) (Research, Society and Development, 2021)
Synthetic dyes are widely used in various industrial sectors, generating a potential pollutant to water bodies. Thus, with a great need to carry out an adequate treatment of this type of effluent, this study observed the efficiency in the removal of the malachite green dye using the activated carbon (AC) produced from the açaí stone (Euterpe oleracea), as an adsorbent. commonly generated in the Amazon region. In the production of AC two activating agents were used, Phosphoric Acid (H3PO4), being called CAG-A and sodium hydroxide (NaOH), being called CAG-B. The AC characterization was performed through FTIR, ATG/ATD, BET area, and SEM/EDS analyzes. To determine the adsorption capacity as well as to study and understand the mechanisms and controlling steps of the adsorption process, the experimental data were adjusted to the mathematical models of Langmuir and Freundlich and to the kinetic models of Pseudo-First Order, Pseudo-Second Order and Intraparticle Diffusion. The analysis for the characterization of the AC’s indicated the presence of acid functional groups, negatively charging the surface of CAG-A and CAG-B, favoring the adsorption process, since the adsorbate in this study is a cationic dye. The experimental data for both CAG-A and CAG-B best fit the Freundlich isotherm, as well as the kinetic model of Pseudo-Second Order had better fit on both coals. The adsorption of malachite green in CAG-A and CAG-B proved to be efficient for ACs, obtaining values ​​of qmax = 113.9 mg/g and 668.88 mg/g respectively.